Vaccination policy in Italy: An update - Stefano Crenna; Antonio Osculati; Silvia D. Visonà (SAGE Publishing, 2018)
The effective control of vaccine-preventable diseases generally requires indefinite maintenance of extremely high rates of timely vaccination. Therefore, vaccine hesitancy is of paramount importance and needs to be addressed. In Italy, regulations about vaccinations are controversial and, to some extent, inconsistent. Even though the childhood vaccinations are mandatory by law (Italian Law n. 891/1939, n. 292/1963, n.51/1966 and n. 165/1991), the limited deterrent effectiveness of the sanctioning system, and the changes introduced by the Italian Constitutional Law n. 3/2001 (devolution of almost all the competences and responsibilities in health matters to the Regions and the Autonomous Provinces), were the fertile ground in which new vaccine policies were generated and developed, radically different from the existing ones: many Regions, based on what was decided in 2005 - on an experimental basis - by the State-Regions Conference, decided to abolish the vaccination obligation and/or to stop the imposition of administrative sanctions on non-compliant parents. In addition, since then, there is a worrying tendency to decline vaccinations due to the parents' mistrust in pharmaceutical companies and health policies. Therefore, recently, the Italian government decided to deploy an emergency ordinance (Italian Decree Law n. 73/2017). In this article, the authors are going to illustrate the current situation in Italy concerning vaccination policy, from a legislative and social point of view.